2008
DOI: 10.1016/j.bbamcr.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

S100A8/9 induces cell death via a novel, RAGE-independent pathway that involves selective release of Smac/DIABLO and Omi/HtrA2

Abstract: A complex of two S100 EF-hand calcium-binding proteins S100A8/A9 induces apoptosis in various cells, especially tumor cells. Using several cell lines, we have shown that S100A8/A9-induced cell death is not mediated by the receptor for advanced glycation endproducts (RAGE), a receptor previously demonstrated to engage S100 proteins. Investigation of cell lines either deficient in, or over-expressing components of the death signaling machinery provided insight into the S100A8/A9-mediated cell death pathway. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 66 publications
11
114
3
1
Order By: Relevance
“…These results suggest that extracellular S100A8/A9 promote migration and invasion through interaction with gastric cancer cells. Although S100A8/A9 protein has been shown to exert apoptotic effect against various tumor cells including colon carcinoma cells (Ghavami et al, 2004) and breast cancer cells and neuroblastoma cells (Ghavami et al, 2008a), the effect of S100A8/ A9 on cell viability has been reported to be dependent on concentration exposed. S100A8/A9 resulted in significantly reduced cell viability at concentration above 50 μg/ml, while it at concentration lower than 25 μg/ml promotes proliferation and migration of various cancer cells (Ghavami et al, 2008b;Hermani et al, 2006;Moon et al, 2008).…”
Section: A B Cmentioning
confidence: 99%
“…These results suggest that extracellular S100A8/A9 promote migration and invasion through interaction with gastric cancer cells. Although S100A8/A9 protein has been shown to exert apoptotic effect against various tumor cells including colon carcinoma cells (Ghavami et al, 2004) and breast cancer cells and neuroblastoma cells (Ghavami et al, 2008a), the effect of S100A8/ A9 on cell viability has been reported to be dependent on concentration exposed. S100A8/A9 resulted in significantly reduced cell viability at concentration above 50 μg/ml, while it at concentration lower than 25 μg/ml promotes proliferation and migration of various cancer cells (Ghavami et al, 2008b;Hermani et al, 2006;Moon et al, 2008).…”
Section: A B Cmentioning
confidence: 99%
“…The majority of these myosins are actively involved in cell assembly and organization or cytoskeleton reorganization. Among the several significantly down-regulated proteins, we found at least three proteins, S100A8, S100A9, and PIP, of specific interest because their expression is associated with a decrease of cell proliferation and induction of apoptosis (29,30). The two S100 EF-hand calcium-binding proteins S100A8/A9 induce apoptosis in various cells, especially tumor cells like MCF-7 (29).…”
Section: Optimization Of Experimental Protocol and Receptor Expressiomentioning
confidence: 99%
“…At present, conventional anticancer therapies include chemotherapy, radiation and immunotherapy [97][98][99] and kill rapidly growing differentiated tumor cells, thus reducing tumor mass but potentially leaving behind cancer-initiating cells (Box 2). Therapies that exclusively address the pool of differentiated cancer cells but fail to eradicate the CSC compartment might ultimately result in relapse and the proliferation of therapy-resistant and more aggressive tumor cells, causing the death of the patient.…”
Section: Cscs and Implications For Therapeutic Applicationsmentioning
confidence: 99%